Climate change and cattle farming - Statham, Jonathan M.E.; Green, Martin J.; Husband, James; Huxley, J.N. (BMJ Publishing Group, 2017)
Issues raised by cattle farming in relation to climate change extend beyond discussion of greenhouse gas emissions and global warming. There are profound consequences for water availability, soil degradation, biodiversity and local ecology, as well as in terms of conflict for energy supplies. Although climate change impacts on cattle farming (through effects on water availability, heat stress and flooding, for example), this article focuses on how cattle farming impacts on climate change. It explores the issues in terms of the impact of cattle farming on the environment, and how to measure and reduce climate change impacts at farm level. Managing the complex and conflicting balance of factors required for sustainable food production offers an important role for the veterinary surgeon.